Effect of Astaxanthin on Tissue Transglutaminase and Cytoskeletal Protein Expression in Amyloid-Beta Stressed Olfactory Ensheathing Cells: Molecular and Delayed Luminescence Studies - Agatina Campisi; Giovanni Sposito; Rosaria Grasso; Julia Bisicchia; Michela Spatuzza; Giuseppina Raciti; Agata Scordino; Rosalia Pellitteri (MDPI AG, 2023)
Astaxanthin, a natural compound of Haematococcus pluvialis, possesses antioxidant, anti-inflammatory, anti-tumor and immunomodulatory activities. It also represents a potential therapeutic in Alzheimer's disease (AD), that is related to oxidative stress and agglomeration of proteins such as amyloid-beta (Aβ). Aβ is a neurotoxic protein and a substrate of tissue transglutaminase (TG2), an ubiquitary protein involved in AD. Herein, the effect of astaxanthin pretreatment on olfactory ensheathing cells (OECs) exposed to Aβ(1-42) or by Aβ(25-35) or Aβ(35-25), and on TG2 expression were assessed. Vimentin, GFAP, nestin, cyclin D1 and caspase-3 were evaluated. ROS levels and the percentage of cell viability were also detected. In parallel, delayed luminescence (DL) was used to monitor mitochondrial status. ASTA reduced TG2, GFAP and vimentin overexpression, inhibiting cyclin D1 levels and apoptotic pathway activation which induced an increase in the nestin levels. In addition, significant changes in DL intensities were particularly observed in OECs exposed to Aβ toxic fragment (25-35), that completely disappear when OECs were pre-incubated in astaxantin. Therefore, we suggest that ASTA pre-treatment might represent an innovative mechanism to contrast TG2 overexpression in AD.